Model Pengembangan Kurikulum dan Proses Belajar-Mengajar di ITB dalam Mencetak Teknoprener bagi Kemajuan Bangsa Indonesia dan Pembangunan Nasional Berkelanjutan - Anggiat BP Sinaga (Fakultas Seni Rupa dan Desain ITB, 2006)
Currently, national education system is still incapable to provide meaningful contribution to the advancement of Indonesia's nation. It is mirrored on the teaching system at ITB, education here can not forge learners to become agents of innovation for development & prosperity to the Indonesian-national community. Refferring to